Hepatitis B virus infection among 5 493 migrant workers in Shenzhen city's Luohu Demonstration Zone for comprehensive hepatitis B prevention and treatment - Fang ZHU; Xiang-dong YIN; Gang LIU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the prevalence of hepatitis B virus (HBV) infection among migrant workers in Luohu district of Shenzhen city for providing evidences to HBV infection prevention in the workers. Methods A questionnaire survey and serum hepatitis B surface antigen (HBsAg) and antibody (anti-HBs) detections with enzyme-linked immunosobent assay (ELISA) were conducted among 5 493 migrant workers in Shenzheng city's Luohu demonstration zone for comprehensive prevention and control of hepatitis B (HB) when the workers had their physical examinations between April 2019 and June 2020. Results For all the workers, the positive rate was 6.54% and 60.37% for serum HBsAg and anti-HBs; the positive rate of both HBsAg and anti-HBs differed significantly by age, education, occupation, registered residence, and history of HBV vaccination. The results of binary logistic regression analysis on significant influencing factors of serum HBsAg and anti-HBs identified with univariate analysis demonstrated that inoculation of HBV vaccine is a protective factor against HBsAg positive; while, with the education of junior high school and lower and aged 30 - 49 years are risk factors for HBsAg positive; the results also indicated that the workers having received HBV vaccination, aged less than 30 years, and with a registered residence in East China were more likely to be serum anti-HBs positive compared to other migrant workers. ConclusionThe prevalence of HBV infection decreased in comparison to that ten years ago among migrant workers in Shenzhen city's Luohu demonstration zone for comprehensive HBV infection prevention and treatment but the prevention of HBV infection still needs to be strengthened in the unvaccinated migrant workers younger than 20 years and in those from southwest, northeast and northwest region of China.